The Influence of Profitability, Company Size, Operational Complexity, and Leverage on Timeliness of Financial Report Submission (Empirical Study on Manufacturing Companies in Consumption Industry Sector Listed on the Indonesia Stock Exchange in 2018-2020): Pengaruh Profitabilitas, Ukuran Perusahaan,Kompleksitas Operasi, dan Leverage Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan (Studi Empiris pada Perusahaan Manufaktur Sektor Industri Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun - Kusumadewi, Sinta Ayu; Aris, Muhammad Abdul (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to examine the effect of profitability, firm size, operating complexity and leverage on the timeliness of financial statement submission. This study uses a purposive sampling method, in manufacturing companies in the consumption industry sector listed on the Indonesia Stock Exchange in 2018-2020. This study uses multiple linear regression with the analytical techniques used are classical assumption test, model feasibility test and hypothesis testing (t test). The results of this study indicate that the firm size variable has a positive effect on the timeliness of financial statement submission, while the profitability, operating complexity and leverage variables have a negative effect on the timeliness of financial statement submission.